TINJAUAN YURIDIS TERHADAP FIDUSIA ULANG OBJEK TANPA ROYA FIDUSIA BERDASARKAN UNDANG – UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA - Opia Rendra; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Fiduciary as one form of security institutions are regulated in Law Number 42Year 1999 on Fiduciary expected to meet the legal requirement that can be furtherspur national development and to ensure legal certainty and be able to provide legalprotection for interested parties. However, legal certainty which is the goal of thislegislation is still far from expectations. Roya fiduciary arrangements regardingquestionable to be implemented by all recipients of fiduciary need to beaccommodated immediately. Objects fiduciary guarantee that no fiduciary possibilityroya trigger reset if the object is returned as collateral and this will lead to legalconsequences for fiduciary giver.This type of research can be classified into types of normative legal research isresearch literature, which focused on the discussion of the principles of law. Thisresearch led to the assessment of the legislation is Law Number 42 Year 1999 onFiduciary and other legislation relating to fiduciary.The conclusion that can be derived from the research is the First, the legislationregarding the fiduciary not provide legal certainty associated with Roya fiduciaryobligations as yet firmly in the regulation so that the fiduciary still possible re-occur.Secondly, Effects of fiduciary acts on objects that have not been re roya fiduciaryform a second creditors lose the right preferent and the imposition of criminalpenalties to providers fiduciary fiduciary should be charged to the recipient.Suggestions authors of the problems studied is the First, is expected toimmediately confirm the arrangements regarding fiduciary roya in the legislationconcerning fiduciary for the creation of legal certainty roya fiduciary. The second areexpected to providers fiduciary fiduciary to ensure recipients have done royafiduciary fiduciary to the object in order to escape legal consequences in the form ofcriminal punishment.Keywords : Roya Fidusia-Object Guarantee-Fidusia Repeat